Bibliografia Lubelszczyzny - ogólna bibliografia regionalna = The Bibliography of the Lublin Region - a generał regional bibliography - Lech-Jabłońska, Bożena (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The article presents the history and current state of work on the Bibliography of the Lublin Region, which began in 1963. The bibliography is compiled and publishedby the Hieronim Łopaciński Regional Public Library in Lublin. Methodological assumptions of the bibliography are discussed and the evolution of its compilation forms is presented: from traditional bibliographic files through printed volumes, electronic databases to a common catalogue environment with in the OMNIS e-service project. Ways of popularizing the results of bibliographers' work and presenting bibliographies to users are indicated: thematic files in the main library, paper codes in various libraries, online visible databases and digital libraries. The article presents the importance of regional bibliography in documenting the change staking place in social, political, economic, cultural and scientific life and in preserving information on the achievements of the region and its place in the country for future generations. The merits of preserving the cultural heritage and promoting the region are highlighted. Tasks for the future are also listed determiningthe development and qualitative level of the Bibliography of the Lublin Region.
Keywords: bibliografia regionalna; biblioteki publiczne; Lubelszczyzna; lubliniana; metodyka bibliograficzna; Wojewódzka Biblioteka Publiczna im. Hieronima Łopacińskiego w Lublinie; województwo lubelskie; regional bibliography; public libraries; the Lublin Land; bibliographic methodology; Hieronim Łopaciński Regional Public Library in Lublin; Lubelskie Region